Pouch Surgery — The Importance of the Transitional Zone - IC Lavery; WB Tuckson; VW Fazio; JR Oakley; JM Church; JW Milsom (Canadian Journal of Gastroenterology)
Patients with preservation of the transitional zone of the anal canal have less leakage and less need to wear pads than patients who have had mucosectomy. There is a significant difference in mean maximum resting pressure between patients that have had anal transitional zone preservation and mucosectomy. With preservation of the anal transitional zone, a mean maximum resting pressure of 57.6±3.8 mmHg was obtained compared with 47.3±4 mmHg in the mucosectomy group. Preservation of the resting pressure is dependent on preservation of internal anal sphincter integrity. The integrity of the sphincter is injured during mucosectomy due to anal dilation. Other factors affecting continence and stool frequency, such as diet, antidiarrheal medications, stool consistency and compliance, when examined were found to be unrelated factors.